2003
DOI: 10.1016/s0092-8674(03)00477-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Control of the Releasable Vesicle Pools by SNAP-25 Splice Variants and SNAP-23

Abstract: The SNARE complex, consisting of synaptobrevin, syntaxin, and SNAP-25, is essential for calcium-triggered exocytosis in neurosecretory cells. Little is known, however, about how developmentally regulated isoforms and other cognate SNARE components regulate vesicular fusion. To address this question, we examined neuroexocytosis from chromaffin cells of Snap25 null mice rescued by the two splice variants SNAP-25a and SNAP-25b and the ubiquitously expressed homolog SNAP-23. In the absence of SNAP-25, vesicle dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
344
9
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 324 publications
(396 citation statements)
references
References 42 publications
35
344
9
3
Order By: Relevance
“…We reported previously that the expression of the ubiquitous isoform SNAP-23 in Snap-25 null chromaffin cells supports some rescue of calcium-dependent exocytosis, but without a burst component (Sorensen et al, 2003b). Here, we first repeated this experiment with similar results, and then applied stronger stimulation into the Ͼ100 M range to investigate whether exocytosis in the presence of SNAP-23 might be shifted to higher [Ca 2ϩ ] i and therefore have gone undetected in previous studies.…”
Section: The Snap-25 Linker Domain Speeds Up Exocytosis Triggeringmentioning
confidence: 63%
See 3 more Smart Citations
“…We reported previously that the expression of the ubiquitous isoform SNAP-23 in Snap-25 null chromaffin cells supports some rescue of calcium-dependent exocytosis, but without a burst component (Sorensen et al, 2003b). Here, we first repeated this experiment with similar results, and then applied stronger stimulation into the Ͼ100 M range to investigate whether exocytosis in the presence of SNAP-23 might be shifted to higher [Ca 2ϩ ] i and therefore have gone undetected in previous studies.…”
Section: The Snap-25 Linker Domain Speeds Up Exocytosis Triggeringmentioning
confidence: 63%
“…Primary culture of mouse chromaffin cells was prepared and cultured as described previously (Sorensen et al, 2003b). SNAP-25a cysteine mutants and SNAP-25a/SNAP-23 chimeras were produced by polymerase chain reaction (PCR), and all constructs were verified by DNA sequencing.…”
Section: Cell Culture and Expression Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, SNAP25 is a presynaptic plasma membrane protein essential for the triggering of vesicular fusion and neurotransmitter release. 12,13 Second, postmortem studies have shown modifica-tions of SNAP25 protein levels in some brain regions of bipolar patients. 14,15 Third, SNAP25 gene has been widely associated with attention-deficit hyperactivity disorder (ADHD), which is known to share genetic susceptibility with early-onset BD.…”
Section: Introductionmentioning
confidence: 99%